2010
DOI: 10.1016/j.visres.2010.04.009
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between macular pigment and visual performance

Abstract: This study was designed to assess whether macular pigment optical density (MPOD) is associated with visual performance. One hundred and forty-two young healthy subjects were recruited. Macular pigment optical density and visual performance were assessed by psychophysical tests including best corrected visual acuity (BCVA), mesopic and photopic contrast sensitivity, glare sensitivity, photostress recovery time (PRT). Measures of central visual function, including BCVA and contrast sensitivity, were positively a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
74
2

Year Published

2011
2011
2015
2015

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 83 publications
(86 citation statements)
references
References 43 publications
8
74
2
Order By: Relevance
“…MP is a blue light filter (Snodderly et al, 1984b) and a powerful antioxidant, (Khachik et al, 1997) and is therefore believed to protect against age-related macular degeneration (AMD), which is now the most common cause of blind registration in the western world (Klaver et al, 1998). In addition, MP's putative ability to enhance visual performance and comfort is also of interest (Bartlett and Eperjesi, 2008;Engles et al, 2007;Hammond and Wooten, 2005;Kvansakul et al, 2006;Loughman et al, 2010;Nolan et al, 2011;Rodriguez-Carmona et al, 2006;Hammond, 2007, 2008;Stringham et al, 2004;Wooten and Hammond, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…MP is a blue light filter (Snodderly et al, 1984b) and a powerful antioxidant, (Khachik et al, 1997) and is therefore believed to protect against age-related macular degeneration (AMD), which is now the most common cause of blind registration in the western world (Klaver et al, 1998). In addition, MP's putative ability to enhance visual performance and comfort is also of interest (Bartlett and Eperjesi, 2008;Engles et al, 2007;Hammond and Wooten, 2005;Kvansakul et al, 2006;Loughman et al, 2010;Nolan et al, 2011;Rodriguez-Carmona et al, 2006;Hammond, 2007, 2008;Stringham et al, 2004;Wooten and Hammond, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Many cross-sectional studies have shown a positive association between MP and measures of visual performance, including visual acuity, contrast sensitivity (CS), photostress recovery and glare disability (among others). [31][32][33][34][35] It has also been shown that supplementation with the macular carotenoids improves parameters of visual function in patients afflicted with the early form of this condition. [36][37][38] However, no study has yet investigated the impact of a formulation containing MZ on visual function in subjects with early AMD, or on the natural course of this condition.…”
mentioning
confidence: 99%
“…The extent of macular pigmentation has recently been found to be related to the width of the foveal cup, as assessed by optical coherence tomography 3 . Since these pigments are located in the fibers of Henle at the foveola and in the inner nuclear layer beyond the foveola 4 , they act as a prereceptoral filter and are believed to contribute a variety of potentially beneficial properties for vision, including reduction of the effects of chromatic aberration 5 (though not supported by Engles et al 6 ,), improvement of spatial vision and contrast enhancement 7 , increased photopic increment sensitivity 8 , reduced glare sensitivity in some studies 9,10 but not others 11 , and increased critical flicker frequency 12 .…”
mentioning
confidence: 99%
“…The objective of the present study was to evaluate, in a cross sectional manner, the associations between color variables and MPOD, using a much larger sample of subjects than in most previous studies and a battery of color assessments rather than relying on a single method of quantification. This study was part of a larger study of the association between MPOD and a wide range of vision parameters 11 .…”
mentioning
confidence: 99%